A review of mantle xenoliths in volcanic rocks from southern Victoria Land, Antarctica - Adam P. Martin (2844254); A.F. Cooper (9002372); C.L. Doherty (10722747); J.A. Gamble (9610844) (2021)
A compilation of published mineral and whole rock chemistry of mantle xenoliths of 107 southern Victoria Land